K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 12 2017

(x:3-4).5=15

=> x:3-4 = 3

=> x : 3  = 7

=> x       = 7 x 3 = 21

128 - 3(x+4) = 23

=> 3(x+4) = 128 - 23 = 105

=> x + 4 = 105 : 3 = 35

=>  x       = 35 - 4

=>   x        = 31

14 tháng 12 2017

x=21                                                                                                                                                                                                x=31

9 tháng 12 2016

a, x-7= -5

   x   = (-5)+7

   x = 2

Vậy x = 2

b, 128-3.(x+4)=23

          3.(x+4)=128-23

          3.(x+4)= 105

             x+4  = 105 : 3

             x+4  = 35

             x      =  35-4

             x      = 31

Vậy x =31

c, [(6x-39) :7].4=12

    [(6x-39):7]   = 12:4

    [(6x-39):7]   =  3

     6x-39        = 3.7

     6x - 39      =  21

     6x             = 21+39

     6x             = 60              

       x             = 60:6

       x             = 10 

Vậy x = 10

d, (x:3-4).5=15

    x:3-4   = 15 : 5

    x:3-4   = 3

    x: 3      = 7

    x          = 21

Vậy x= 21

9 tháng 12 2016

giúp mk với

2 tháng 12 2017

a) (x : 3 - 4) . 5 = 15

x : 3 - 4 = 15 : 5

x : 3 - 4 = 3

x : 3 = 3 + 4

x : 3 = 7

x = 7 . 3

x = 21.

b) 128 - 3 . (x + 4) = 23

3 . (x + 4) = 128 - 23

3 . (x + 4) = 105

x + 4 = 105 : 3

x + 4 = 35

x = 35 - 4

x = 31.

c) (3x - 24) . 73 = 2 . 74

3x - 24 = 2 . 74 : 73

3x - 24 = 2 . 7

3x - 16 = 14

3x = 14 + 16

3x = 30

x = 30 : 3

x = 10.

d) 5x + x = 39 - 311 : 39

5x + x = 39 - 32

5x + x = 39 - 9

6x = 30

x = 30 : 6

x = 5.

2 tháng 12 2017

a) \(\left(\dfrac{x}{3}-4\right).5=15\)

\(\Leftrightarrow\dfrac{x}{3}-4=\dfrac{15}{5}\)

\(\Leftrightarrow\dfrac{x}{3}-4=3\)

\(\Leftrightarrow\dfrac{x}{3}=3+4\)

\(\Leftrightarrow\dfrac{x}{3}=7\)

\(\Leftrightarrow x=7.3\)

\(\Leftrightarrow x=21\)

Vậy \(x=21\)

b) \(128-3\left(x+4\right)=23\)

\(\Leftrightarrow3\left(x+4\right)=128-23\)

\(\Leftrightarrow3\left(x+4\right)=105\)

\(\Leftrightarrow x+4=\dfrac{105}{3}\)

\(\Leftrightarrow x+4=35\)

\(\Leftrightarrow x=35-4\)

\(\Leftrightarrow x=31\)

Vậy \(x=31\)

c) \(\left(3x-2^4\right).7^3=2.7^4\)

\(\Leftrightarrow3x-2^4=\dfrac{2.7^4}{7^3}\)

\(\Leftrightarrow3x-2^4=2.7\)

\(\Leftrightarrow3x-2^4=14\)

\(\Leftrightarrow3x-16=14\)

\(\Leftrightarrow3x=14+16\)

\(\Leftrightarrow3x=30\)

\(\Leftrightarrow x=\dfrac{30}{3}\)

\(\Leftrightarrow x=10\)

Vậy \(x=10\)

d) \(5x+x=39-3^{11}:3^9\)

\(\Leftrightarrow6x=39-3^{11-9}\)

\(\Leftrightarrow6x=39-3^2\)

\(\Leftrightarrow6x=39-9\)

\(\Leftrightarrow6x=30\)

\(\Leftrightarrow x=\dfrac{30}{6}\)

\(\Leftrightarrow x=5\)

Vậy \(x=5\)

31 tháng 8 2017

\(\frac{x}{2}+x+\frac{x}{3}+x+x+\frac{x}{4}=\frac{23}{12}\)

\(\left(\frac{x}{2}+\frac{x}{3}+\frac{x}{4}\right)+\left(x+x+x\right)=\frac{23}{12}\)

\(\frac{3x}{12}+\frac{36x}{12}=\frac{23}{12}\)

\(\frac{49x}{12}=\frac{23}{12}\)

\(\frac{49}{12}.x=\frac{23}{12}\)

          \(x=\frac{23}{12}:\frac{49}{12}=\frac{23}{49}\)

a, 128 - 3.( x + 4 ) = 23                       b,    [( 6x - 39 ) : 7 ] . 4 = 12                              c,  ( x : 3 - 4 ) . 5 = 15 

    3. ( x + 4 ) = 128 - 23                             [(6x - 39 ) : 7 ] = 3                                           ( x : 3 - 4 ) = 3 

    3. ( x + 4 ) = 105                                    ( 6x - 39 ) = 21                                                   x : 3 = 7

     x + 4 = 35                                               6x = 21 + 39                                                     x = 7 . 3

     x = 35 - 4                                                6x = 60                                                              x = 21 

     x = 31                                                       x = 10                                                         Vậy x = 21

Vậy x = 31                                               Vậy x = 10                            

29 tháng 1 2020

Trl:

a. 128 - 3 . ( x + 4 ) = 23

=> 3 . ( x + 4 ) = 128 - 23

=> 3 . ( x + 4 ) = 105

=> x + 4 = 105 : 3

=> x + 4 = 35

=> x = 35 - 4

=> x = 31

Vậy x = 31

b. [( 6x - 39 ) : 7 ] . 4 = 12

=> [( 6x - 39 ) : 7 ] = 12 : 4

=> [( 6x - 39 ) : 7 ] = 3

=> ( 6x - 39 ) = 3 . 7

=> (  6x - 39 ) = 21

=> 6x = 21 + 39

=> 6x = 60

=> x = 60 : 6

=> x = 10

Vậy x = 10

c. ( x : 3 - 4 ) . 5 = 15

=> ( x : 3 - 4 ) = 15 : 5

=> ( x :3 - 4 ) = 3

=> x : 3 = 3 + 4

=> x : 3 = 7

=> x = 7 . 3

=> x = 21

Vậy x = 21

d. | x + 2 | = 0

=> x + 2 = 0

=> x = 0 - 2

=> x = -2

Vậy x = -2

e. | x - 5 | = |-7|

=> | x - 5 | = 7

=> x - 5 = 7 hoặc x - 5 = -7

=> x = 7 + 5 hoặc x = -7 + 5

=> x = 12 hoặc x = -2

Vậy \(x\in\left\{12;-2\right\}\)

2 tháng 10 2021

giúp me được ko

9 tháng 12 2018

a) 128-3(x+4)=23

3(x+4)=128-23

3(x+4)=105

x+4=105:3

x+4=35

x=35-4

x=31

b) [(4x+28).3+55]:5=35

(4x+28).3+55=35.5

(4x+28).3+55=175

(4x+28).3=175-55

(4x+28).3=120

4x+28=120:3

4x+28=40

4x=40+28

4x=68

x=68:4

x=17

c) ( 12x  - 43 ) . 83 = 4 . 84

12x-64=4.(84:83)

12x-64=4.8

12x-64=32

12x=32+64

12x=96

x=96:12

x=8

d) 720 : [ 4 - ( 2x - 5 ) ] = 23 . 5

720:[4-(2x-5)] = 8.5

720:[4-(2x-5)]=40

4-(2x-5)=720:40

4-(2x-5)=18

2x-5=4-18

2x-5=-14

2x=-14+5

2x=-9

x=-9:2

x=\(\frac{-9}{2}\)

25 tháng 1 2018

1/(-37) +14+26+37

=[(-37)+37] +(14+26)

=       0       +   40

=    40

2/(-24) +6 +10+24

=[(-24)+24] +(10+6)

=     0         +16

=16

3/15+23+9+(-25) +9+(-23)

=[(-23)+23] +[(-25)+15] +(9+9)

=     0         +       (-10)    +18

=     0         +           8

=   8

4/60 +33 +(-50) +(-33)

 =[(-33)+33]+[60 +(-50)]

=    0          +   10

=    10

5/(-16)+ (-209) + (-14) +209

=[(-209)+209] +[(-16)+(-14)]

=     0              +(-30)

=      -30

6/(-12) +(-13)+36 +(-11)

  =[(-12) +(-11)] +[ 36+(-13)]

 =        (-23)       +       23

=     0

 Chúc bn hok tốt !!!

1 tháng 2 2019

1, (-37)+14+26+37=[(-37)+37]+14+26=0+40=40

2, (-24)+6+10+24=[(-24)+24]+6+10=0+16=16

3 , 15+23+(-25)+(-23)=[15+(-25)]+[23+(-23)]=-10

4, 60+33+(-50)+(-33)= [60+(-50)]+[33+(-33)]=10

5, (-16)+(-209)+(-14)+209=[(-16)+(-14)]+[(-209)+209]=-30

6, (-12)+(-13)+36+(-11)=[(-12)+(-11)]+[(-13)+36]=(-23)+23=0

\(\left|x+2\right|=0\)

\(\Rightarrow x+2=0\)

\(\Rightarrow x=0-2\)

\(\Rightarrow x=-2\)

\(\left|x-5\right|=\left|-7\right|\)

\(\Rightarrow\left|x-5\right|=7\)

\(\Rightarrow\hept{\begin{cases}x-5=-7\\x-5=7\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-7+5\\x=7+5\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-2\\x=12\end{cases}}\)

\(\Rightarrow x\in\left\{-2;12\right\}\)